Trends and motives in the post-graduate professional orientation of the young doctors of the 2023 class of Medical University-Sofia - Vidin Kirkov; Alexandrina Vodenicharova; Kremena Ivanova; Krasimira Markova (Pensoft Publishers, 2024)
The grown-up individual's need for self-affirmation is a unified whole with his professional and labor activity and with the successful realization in it. For this reason, professional choice is a complex decision-making process, determined by social and personal factors, as it is dictated not only by the needs of society, but also by the interests, opportunities, needs and inclinations of the individual. In view of this, the present article will present and analyze data from an empirical study investigating the trends, motives and conditions in the professional orientation of young doctors of the 2023 Class of Medical university-Sofia.